Scabies Among Adolescents in Islamic Religious Boarding Schools: A Descriptive Study - Ikbal Fradianto; Nadia Rahmawati; Nurmainah Nurmainah; Mita Mita; I Made Moh. Yanuar Saifudin (GLOBAL HEALTH SCIENCE GROUP, 2024)
Scabies is a common skin infestation caused by mite, posing significant health challenges, especially in densely populated environments like boarding schools. Objective: This study aimed to identify the incidence of scabies among adolescents in Islamic religious boarding schools in Pontianak, Indonesia. Methods: A quantitative descriptive design was employed, involving 220 students from an Islamic boarding school in Pontianak. Concecutive sampling was used to select participants. Data were collected using questionnaires on knowledge and attitudes about scabies, and observation sheets for environmental assessment. Descriptive statistics was performed. Results: The study found that 66.3% of respondents experienced low severity scabies symptoms, while 33.6% had high severity symptoms. The majority of respondents were female (55%), with a mean age of 13.6 years. Knowledge about scabies was generally low, with significant gaps in understanding symptoms, transmission, and prevention. Attitudes towards scabies prevention were also poor, with many students neglecting personal hygiene and environmental cleanliness. Conclusion: The high prevalence of scabies in the boarding school highlights the need for targeted interventions. Future research should focus on evaluating the effectiveness of these interventions to develop sustainable solutions for managing scabies in similar settings.